What is relationship between tooth loss and TMD signs and symptoms in the elderly during the COVID-19 pandemic? (Research, Society and Development, 2022)
Aim: To investigate the relationship between signs and symptoms of temporomandibular disorders (TMD) and teeth loss in the elderly. Method: This research was carried out remotely during July and August 2021. The elderly answered a form that addressed personal aspects, information on general health data, self-perception about the chewing function, facial pain and self-perception about TMD signs and symptoms. Data were stored in Office 2019 Excel spreadsheets. The analysis was performed using descriptive and inferential statistics using the Fisher test using the Statistical Package for Social Sciences (SPSS) 20.0. considering 95% significance. Results: 50 elderly participated in the study, 39 females and 11 males. Most had at least one sign and symptom of TMD, in addition to tooth loss. Self-perception of health can be influenced by social, cultural, emotional and economic issues. Generally, elderly people tend to perceive their oral health in a very positive way, influencing the results. Conclusion: The self-perception of health and the identification of the main needs and complaints of the elderly can be valid as a means to create new public policies for this population. It was possible to identify that cracking when opening the mouth and the indifference in the picture of worsening or improving pain in the pandemic are directly related to tooth loss.